A study on the role of muscle contraction on the self-sustained oscillations of the pharyngoesophageal segment in tracheoesophageal speech - Tourinho, André Miazaki da Costa (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2022.